2008
DOI: 10.1002/joc.1681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and adaptation of a regional climate model for the Horn of Africa: rainfall climatology and interannual variability

Abstract: This study evaluates the ability of the Abdus Salam International Center for Theoretical Physics (ICTP) version 3 Regional Climate Model (RegCM3) to reproduce the observed rainfall amounts and distribution over the topographically varied region of the Horn of Africa. Simulations are performed for the widespread very dry 1984 and locally very wet 1996 years using all of the alternative convective schemes available in the ICTP RegCM3. Extensive comparisons of simulations for 1984 and 1996 reveal that the Emanuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 41 publications
4
52
0
8
Order By: Relevance
“…Consequently, Eritrea averages only about 600 mm of rain in June-August (Kidanemariam, 2003) whereas the much wetter Ethiopian highlands have a mean monsoon season rainfall of more than 1400 mm (e.g. Figure 1 of Segele and Lamb, 2005; Figure 7 of Segele et al, 2008). The main rain zone is associated with the strongest low-level convergence (Figure 3(a) and (b)) and upper tropospheric divergence (Figure 3(d)), and coincides with areas of weaker but deeper ascending motion west of 40-42°E (west of the upper level subsiding current in Figure 4(a)) and south of 10-12°S (Figure 4(b)).…”
Section: Large-scale Atmospheric Circulation Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Eritrea averages only about 600 mm of rain in June-August (Kidanemariam, 2003) whereas the much wetter Ethiopian highlands have a mean monsoon season rainfall of more than 1400 mm (e.g. Figure 1 of Segele and Lamb, 2005; Figure 7 of Segele et al, 2008). The main rain zone is associated with the strongest low-level convergence (Figure 3(a) and (b)) and upper tropospheric divergence (Figure 3(d)), and coincides with areas of weaker but deeper ascending motion west of 40-42°E (west of the upper level subsiding current in Figure 4(a)) and south of 10-12°S (Figure 4(b)).…”
Section: Large-scale Atmospheric Circulation Climatologymentioning
confidence: 99%
“…This area of large water vapour transport divergence includes western Ethiopia, which receives the highest summer rainfall totals (e.g. Figure 1 of Segele and Lamb, 2005; Figure 7 of Segele et al, 2008). This disparity may result from much of Ethiopian summer rainfall being produced more by westward propagating convective systems that intensify locally due to orographic ascent rather than from in situ convection (Segele and Lamb, 2005).…”
Section: Water Vapourmentioning
confidence: 99%
“…Globally, there has been a marked increase in the number of RCM simulations (Alley et al 2007); however, very few RCM studies have been performed over the East African region (Sun et al 1999a;Indeje et al 2000;Anyah, 2005;Anyah et al 2006;Anyah and Semazzi 2006;Anyah and Semazzi, 2007;Segele et al 2009a;Diro et al 2012), and these studies are largely based on the results from a single RCM. However, each model has its strengths and weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Through sensitivity analysis, the authors showed that the parameter lo which determines the amount of condensed water that ultimately falls out as rain has the most direct impact on simulated rainfall amounts. Adjustment of this key parameter (see [9]) substantially improved simulated rainfall amounts using the Emanuel scheme. The temporal correlation between customized model-simulated and observed station rainfall (Figure 1) was +0.66 [9].…”
mentioning
confidence: 99%
“…Based on such assessment, Segele et al [9] showed that RegCM3 overestimated observed rainfall in the Horn of Africa when using the Emanuel scheme. To improve model agreement, the authors varied model parameters that controlled the rate of convective mass flux adjustment (α), the fraction of condensed water that can be converted to precipitation, and the heating and moistening characteristics of the environment (σs, σd).…”
mentioning
confidence: 99%